ANALISIS EFEKTIVITAS DAN KONTRIBUSI SEWA ASET BANGUNAN NEGARA TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur) - Ramadhan, Putra Dwi (EKONOMIA, 2019)
The purpose of this paper is to analyze the Effectiveness and Contribution of State Buildingsâ€™ Asset Leases on Local Government Revenue (A Case Study in Human Resources Development Agency of East Kalimantan Province). The problems of the study are stated as follows: (1) Does the lease of state building assets in the Human Resources Development Agency of East Kalimantan Province have reached the expected level of effectiveness in 2013 - 2017? (2) Does the lease of state building assets the Human Resources Development Agency of East Kalimantan Province achieve the level of expected contribution to local government revenue?Effectiveness is the achievement of a goal in a good way and resulted well which has done by a person, a group or an organization. Contribution is an analyze tool that is used to find out how much contribution can be made from renting buildings assets towards Local Government Revenue. The researchâ€™s hypothesis are: (1) Income from state building assets lease in the Human Resources Development Agency has not reached the expected level of effectiveness in the period of 2013- 2017. (2) Income from state building assets lease to the Human Resources Development Agency has not reached the level of expected contribution to the Local Government Revenue Income for the 2013-2017 period.The data analysis technique used in this study was the analysis of Effectiveness Ratio and Contribution Ratio. The results of the research on the effectiveness and contribution to Local Government Revenue in the Human Resource Development agency in East Kalimantan Province as measured by the ratio of effectiveness and contribution in 2013 - 2017. The Human Resource Development agency of East Kalimantan province has succeeded in optimizing the effectiveness of leasing its building assets, and for the level of contribution towards Local Government Revenue is still considered too low, but it does not mean it was insignificant because the source of local revenue itself comes from taxes - local taxes, regional retribution, the share of profits of â€œBUMDâ€ and other incomes